PENGARUH CURRENT RATIO, DEBT TO ASSETS RATIO, DAN RETURN ON ASSETS TERHADAP KONDISI FINANCIAL DISTRESS DIMASA COVID-19 PADA PERUSAHAAN TRANPORTASI YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) 2018 - 2022 - Fadli Rojulmubin; Tri Sulistyani (Journal of Research and Publication Innovation, 2024)
This study aims to analyze the influence of the current ratio, debt to assets ratio, and return on assets on financial distress conditions in transportation sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. The method used in this research is quantitative, using secondary data collection. The sampling technique employed is purposive sampling based on certain criteria, resulting in 18 companies as the research sample. The analysis technique uses multiple linear regression with the assistance of IBM SPSS Statistics 25. The results of the study indicate that liquidity (current ratio) has a positive and significant effect on financial distress, with a t-value of 11.596, which is greater than the t-table value of 1.98793 and a significance value of 0.000 < 0.050. Solvency (debt to assets ratio) has a negative and significant effect on financial distress, with a t-value of -17.516, which is greater than the t-table value of -1.98793 and a significance value of 0.000 < 0.050. Profitability (return on assets) also has a positive and significant effect on financial distress, with a t-value of 11.787, which is greater than the t-table value of 1.98793 and a significance value of 0.000 < 0.050. Simultaneously, the variables of liquidity, solvency, and profitability have a positive and significant effect on financial distress, with an F-value of 466.098, which is greater than the F-table value of 1.98793 and an F significance level of 0.000 < 0.050..